Karakteristik Organoleptik Cookies Tepung Kernel - Tika Haryanti; Marselus Hendro; Yuni Selvianti Sari (Politeknik Negeri Lhokseumawe, 2026)
Cookies are a type of biscuit with a crisp texture and low moisture content; the primary ingredient used in their production is kernel flour. The cookie-making process involves mixing the dough, shaping the dough (foaming), and baking (haking). This study aims to determine the characteristics of Cookies made with kernel flour substitution based on analysis of sensory properties (aroma, color, texture, and taste) as assessed by hedonic testing. This study employed a factorial design comparing the ratios of kernel flour to wheat flour used in cookie production, with four treatments: (K = 200 g kernel flour : 0 g wheat flour, P1 = 40 g kernel flour : 160 g wheat flour, P2 = 80 g kernel flour : 120 g wheat flour, and P3 = 120 g kernel flour : 80 g wheat flour). The results of the sensory of Cookies made with kernel flour substitution showed that the substitution had a significant effect on the sensory properties of the resulting Cookies; specifically, each sample differed significantly (calculated F table F at 5%) in terms of colour, aroma, taste, and texture. The most preferred cookie (average preference score of 6.0000) was the one with 40% kernel flour added.